Operation of Building Objects Based on the Informational Model - E. V. Borsuk; A. S. Davidovich (Цифровая трансформация, 2019)
This article reviews and assesses the possibilities and features of the application of information modeling technology at such an important stage of work as the operation of a building. At present, it becomes more and more obvious that the most promising area of research in the field of managing socially significant processes, including the exploitation of buildings and structures, is undoubtedly the 3D modeling of objects, which provides truly unlimited possibilities in realistic representation of the surrounding world through 3D modeling. However, at the present stage this direction is still very rarely used in the CIS countries, and the possibilities of computer aided design systems are still underestimated, some of which are discussed in this article.